Coherent Two-dimensional Teaching - Personalistic and Mediatized - a Pedagogical Opportunity and Hope for the Present and the Future - Janusz Miąso (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: Didactics is a pedagogical subdiscipline as well as the constant search for a more constructive and effective teaching process - learning in order to better and more effectively guide each other - teacher - student and at the same time student - teacher. The current popandemic situation and, at the same time, a powerful expansion of new media, including educational media, mobilize for the necessary research, how to constructively use the media in didactics to make it a constructive coexistence. We can see that the new media played a very positive role during the pandemic, because if they did not exist, teaching would probably only become self-education or a lack of education, but at the same time we felt even more the priceless value of real contacts and real education. Research Aim: For truly effective 21st century didactics, invaluable interpersonal contact is necessary, this is the most important for motivation, for the desire to learn effectively together, but this process will also be supported by the media, because mediatization is currently one of the strongest processes and the search for constructive coherence of personalism and mediatization this is the main research problem and research goal. Evidence-based Facts: Research in this area is carried out by many eminent researchers (Carr, Pinker, Spitzer, Dijk, Fukuyama, Gergen, Melosik, Baron-Polańczyk, Morbitzer), but they require constant guidance and intensification, because the times are extremely expansive and dynamic. Summary: To sum up, it should be stated that there is a need for continuous and even more expansive didactic modeling so that this personalistic-mediatized coherence would be as fruitful as possible for man and society, and here a great research and didactic effort is needed.